Analisis Pembelajaran KPK dan FPB Kelas 4 SD - Unaenah, Een; Melyana, Angele; Ummah, Siti Azkiatul (Lembaga Yasin AlSys, 2023)
The purpose of this study was to see how the learning of the Least Common Multiple (KPK) and Greatest Common Factor (FPB) learning is carried out in grade 4 of Elementary School (SD). The concepts of KPK and FPB have important relevance in the development of students' understanding of mathematics, but are often taught fundamentally without regard to prerequisite concepts and variations of effective learning models. In this study, using the literature study method, we explore the concepts of KPK and FPB, effective teaching strategies, and their benefits in developing students' understanding of mathematics. We also identify challenges that may arise in KPK and FPB learning and provide solutions to overcome these challenges. The results of the study found that with a strong understanding of KPK and FPB, students can develop better mathematical skills and be ready to face more complex mathematical concepts in the future. By implementing appropriate teaching strategies and handling challenges that arise, learning from KPK and FPB is expected to improve students' understanding of mathematics in grade 4 elementary school.